2021
DOI: 10.1016/j.redox.2020.101807
|View full text |Cite
|
Sign up to set email alerts
|

FBW7-NRA41-SCD1 axis synchronously regulates apoptosis and ferroptosis in pancreatic cancer cells

Abstract: FBW7 functions as a tumor suppressor by targeting oncoproteins for degradation. Our previous study found FBW7 was low expressed in pancreatic cancer due to sustained activation of Ras-Raf-MEK-ERK pathway, which destabilized FBW7 by phosphorylating at Thr205. MicroPET/CT imaging results revealed that FBW7 substantially decreased 18F-fluorodeoxyglucose uptake in xenograft tumors. Mechanistically, FBW7 inhibited glucose metabolism via c-Myc/TXNIP axis. But in these studies, we observed FBW7 down-regulated genes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 170 publications
(128 citation statements)
references
References 42 publications
5
111
0
Order By: Relevance
“…Mutation of PI3K-AKT-mTOR signaling protects cancer cells from ferroptosis death through SREBP1/SCD1-mediated lipogenesis [33]. Besides, various studies have reported that ferroptosis can mitigate gemcitabine resistance and lead to a favorable prognosis in pancreatic cancer cells [34,35], which is consistent with the result of our study: most of the Fe-LPM are protective factors based on the univariate Cox regression analysis.…”
Section: Discussionsupporting
confidence: 91%
“…Mutation of PI3K-AKT-mTOR signaling protects cancer cells from ferroptosis death through SREBP1/SCD1-mediated lipogenesis [33]. Besides, various studies have reported that ferroptosis can mitigate gemcitabine resistance and lead to a favorable prognosis in pancreatic cancer cells [34,35], which is consistent with the result of our study: most of the Fe-LPM are protective factors based on the univariate Cox regression analysis.…”
Section: Discussionsupporting
confidence: 91%
“…They observed that inhibition of SCD significantly potentiated the antitumor effect of ferroptosis inducers. Ye et al ( 30 ) reported that SCD inhibited both ferroptosis and apoptosis in pancreatic cancer cells. In our study, we verified the aberrant expression of SCD in BLCA tissues and found that samples with high T stage or MIBC expressed higher SCD, which assumed that SCD may play an important oncogenic role in BLCA.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, finding new strategies for comprehensive treatment of pancreatic cancer is urgent. 71 , 72 MA can inhibit human pancreatic cancer Panc‐28 cells with an IC 50 value of 49.2 ± 0.5 μM. MA also significantly induced autophagy at a concentration of 50 μM.…”
Section: Anticancer Properties Of Maslinic Acidmentioning
confidence: 94%